Comparative quantitative analysis of active substances in black chokeberry products available on local market - Pavičić, Nada; Velikinac, Ivan (Archives of Pharmacy, 2022)
In recent decades, black chokeberry (Aronia melanocarpa (Michk.) Elliot) and products derived from its fruit (berries) have increasing popularity and wide applications. On the global and domestic market, chokeberry products are available in the forms of cold-pressed juice, herbal teas, tinctures, as well as food or dietary supplements. A large number of studies have been published in the scientific literature, studying chemical composition, mechanism of action, pharmacological activity and safety of active ingredient. Possibilities for the use of chokeberry pharmaceuticals in diseases and conditions related to oxidative stress are being intensively investigated. It has been proven that polyphenolic compounds are responsible for biological activity: anthocyanins, proanthocyanidins and phenolic acids. There are no official monographs published in modern world pharmacopoeias for herbal drugs and herbal preparations, therefore no standards regarding their qualitative and quantitative composition have been established. The aim of this study was to quantify active ingredients in chokeberry products available in the local pharmacies. The study covered five commercially available products, which the producers declared as 100% organic, mother, or cold-squeezed chokeberry fruit juice. The content of anthocyanins and flavonoids in these products was determined using specific, selective HPLC-UV methods. Other quality parameters: relative density, pH, dry residue, total polyphenols, residual solvents (ethanol), were also included in this examination. The results showed that the quantitative composition of the active compounds in chokeberry products can vary significantly. For example, the content of cyanidin-3-galactoside, as the most represented anthocyanin, ranged from 0.15 g/l to 5.5 g/l.